2001
DOI: 10.1081/ceh-100107390
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes of Aldosterone Synthase (Cyp11b2) Gene in the General Population of Japan: The Ohasama Study

Abstract: Since the identification of a chimeric aldosterone synthase which induces mendelian hypertension, polymorphisms in aldosterone synthase (CYP11B2) has been one of major targets for molecular analyses in association with hypertension. To date, four polymorphic variants of CYP11B2, -344T/C at promoter region, a gene conversion in intron 2, 2713A/G (in exon 3) which converts from Lys to Arg at codon 173 (K173R), and 4986T/C (in exon7) which converts from Val to Ala at codon 386 (V386A), have been identified in Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…We previously reported an absolute linkage disequilibrium between the 344C/T and R173K polymorphisms, and a close linkage between 344T and the intron 2 sequence conversion in the general Japanese population, forming the three allelic haplotypes (13). In this study we failed to find the V386A mutation of CYP11B2 (13), which has been reported in Caucasians (4).…”
Section: Introductioncontrasting
confidence: 52%
See 2 more Smart Citations
“…We previously reported an absolute linkage disequilibrium between the 344C/T and R173K polymorphisms, and a close linkage between 344T and the intron 2 sequence conversion in the general Japanese population, forming the three allelic haplotypes (13). In this study we failed to find the V386A mutation of CYP11B2 (13), which has been reported in Caucasians (4).…”
Section: Introductioncontrasting
confidence: 52%
“…Three genetic polymorphisms of CYP11B2, 344C/T at the promoter region, a conversion in intron 2 from the CYP11B2 sequence to that of CYP11B1, and R173K in exon 3, were examined as reported previously (13). Briefly, 344C/T and R173K polymorphisms were genotyped by polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP), and the presence or absence of intron 2 conversion was determined by allele-specific PCR (13).…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aimed at a comparision between human CYP11B2 carrying a lysine or a arginine, repectively at postion 173, which is a common polymorphism in the CYP11B2 gene [10], in combination with the mutation V386A. Therefore, investigations in a reconsituted in vitro system containing purified CYP11B2, Adx and AdR in HEPES, pH 7.4, were performed.…”
Section: Resultsmentioning
confidence: 99%
“…One of them carries either a lysine or an arginine at position 173 of the amino acid chain. A haplotype study in Japan (547 examined persons) revealed a frequency of 46% for the lysine variant, 45% were heterozygous for lysine and arginine and 9% carried an arginine residue at this position [10]. A comparison of the two CYP11B2 variants was performed by Zhang et al utilizing a cell culture system [12].…”
Section: Discussionmentioning
confidence: 99%